THE STRUGGLE OF INDIGENOUS WOMEN FROM A CRITICAL FEMINIST PERSPECTIVE: A LITERATURE STUDY OF THE INDIGENOUS COMMUNITIES OF LAKE TOBA - Rahmatunnisa, Mudiyati; Cusdiawan, Cusdiawan (JWP (Jurnal Wacana Politik), 2026)
This article explores the struggle of indigenous women in the Lake Toba region through a critical feminist perspective. Critical feminism is employed here not only to analyze the complexity of Indigenous women’s experiences in the Lake Toba region, but also as a theoretical framework for envisioning and advancing Indigenous women’s movements. Using a literature study method, this research analyzes various academic works, reports, and secondary data related to indigenous women, capitalism, patriarchy, and corporatist development. This study argues that indigenous women experience various forms of marginalization caused by the intersection of state-supported capitalist expansion, which has led to the loss of their access to land and healthy living spaces. This capitalist expansion further deepens gender-based injustice, particularly within the context of patriarchal social constructions. The findings show that critical feminism not only provides a framework for understanding these structural inequalities, but also offers a paradigmatic foundation for building more inclusive and emancipatory social movements. Furthermore, critical feminism helps prevent the co-optation of movements by neoliberal capitalist interests and strengthens solidarity among marginalized groups in confronting alliances between corporations and the state. This study contributes to the development of critical feminist discourse in the context of Batak indigenous women and indigenous social movements in the Lake Toba region.